Pharmaceutical Supply Chain Optimization in Healthcare: Insights from Recent Literature - Gulo, Nara Fathina; Aini, Nurul; Jamal, Siti Aisyah (YCMM, 2025)
This study aims to review and synthesize recent literature on the optimization of pharmaceutical supply chains in the healthcare sector. Using a Systematic Literature Review (SLR) approach based on PRISMA guidelines, six peer-reviewed articles published between 2020 and 2025 were analyzed in depth. The findings reveal that optimization models such as Mixed Integer Linear Programming (MILP), and the integration of digital technologies—including Artificial Intelligence (AI), blockchain, and the Internet of Things (IoT)—have significantly improved operational efficiency, transparency, and resilience in pharmaceutical logistics. Additionally, lean-digital strategies and resilience-oriented approaches such as supplier diversification and scenario planning have proven effective in addressing supply chain disruptions. The study also highlights research gaps in real-world implementation and calls for the development of integrated frameworks that are adaptive to the dynamics of global healthcare systems. These findings provide strategic insights for practitioners and researchers aiming to design robust and sustainable pharmaceutical supply chains.